Coagulopathy following Crotaliπae snakebites in northeast Florida. Issue 4 (10th June 2022) - Maharaj, Satish; Seegobin, Karan; Chang, Simone
Abstract : Effects of Crotalinae envenomation vary by geographical areas and research into coagulopathy and effects of antivenom are needed to optimize management. This was a single-center retrospective review with testing on presentation and 4 h after; antivenom administration was noted and data analyzed overall and comparing envenomations. One hundred and nineteen snakebites evaluated with 59 identified as Crotalinae and half receiving antivenom. PT/aPTT was elevated in 20% of water moccasin/copperhead and 21% of rattlesnake bites. DIC-like syndrome occurred in 8% water moccasin/copperhead and 6% rattlesnake bites. Antivenom did not seem to correct PT or aPTT at 4 h follow-up in most cases. Thrombotic microangiopathy was not seen. Coagulopathy was prevalent affecting one in five patients in this cohort and does seem to persist at short interval follow-up, even in those receiving antivenom. We support guidelines recommending clinical monitoring and serial coagulation profiles in such cases. Blood Coagul Fibrinolysis 30:000 – 000 Copyright © 2022 Wolters Kluwer Health, Inc. All rights reserved.